Pengaruh Kualitas Pelayanan, Promosi dan Lokasi Terhadap Kepuasan Pelanggan di Park Hotel Jakarta - Elisabet Crismawati; Chatarina Yunita (Panorama Nusantara, 2022)
The purpose of this study was to determine the effect of service quality, promotion and location on customer satisfaction at Park Hotel Jakarta. The population in this study were all visitors who stayed at Park Hotel Jakarta from April 2022 to May 2022. The sampling technique used was purposive sampling as many as 100 respondents. Collecting data using a questionnaire that has been tested for validity and reliability. The analytical method used in this research is multiple regression analysis. The results of statistical tests can be concluded that the quality of service, promotion and location simultaneously have a significant effect on customer satisfaction. Then the partial results show that the Promotion and Location variables have a significant effect on Customer Satisfaction, while the Service Quality variable has no significant effect on Customer Satisfaction. The result of the coefficient of determination on customer satisfaction is 44.1% and the remaining 55.9% is influenced by other variables that are not included in this study.